ANALISIS NIAT PENGGUNAAN KENDARAAN LISTRIK: PENDEKATAN TEORI PERILAKU TERENCANA DALAM KONTEKS MOBILITAS BERKELANJUTAN - Rini Sari; Aisyah Qanita; Siti Fadila; Febryenda Febryenda; Muhammad Dharma; Ahmad Askar (Universitas Majalengka, 2024)
Although electric vehicles are considered a breakthrough with potential positive impacts on the environment, economy, and public health, their adoption in Indonesia is still low. This study examines the factors that influence the intention to adopt electric vehicles using the theory of planned behavior approach. The theory of planned behavior emphasizes that attitudes, subjective norms, and individual behavioral control play a role in forming the intention to act. Data were obtained from 149 respondents who use motorized vehicles daily and were analyzed using Structural Equation Modeling - Partial Least Square (SEM PLS). The results show that attitudes, subjective norms, and behavioral control partially have a positive and significant effect on the intention to adopt electric vehicles. This study provides important insights for policymakers and industry to promote sustainable mobility in Indonesia.